Mitochondrial Peroxiredoxin 3 Is Rapidly Oxidized and Hyperoxidized by Fatty Acid Hydroperoxides - Giuliana Cardozo; Mauricio Mastrogiovanni; Ari Zeida; Nicolás Viera; Rafael Radi; Aníbal M. Reyes; Madia Trujillo (Antioxidants, 2023)
Human peroxiredoxin 3 (HsPrx3) is a thiol-based peroxidase responsible for the reduction of most hydrogen peroxide and peroxynitrite formed in mitochondria. Mitochondrial disfunction can lead to membrane lipoperoxidation, resulting in the formation of lipid-bound fatty acid hydroperoxides (LFA-OOHs) which can be released to become free fatty acid hydroperoxides (fFA-OOHs). Herein, we report that HsPrx3 is oxidized and hyperoxidized by fFA-OOHs including those derived from arachidonic acid and eicosapentaenoic acid peroxidation at position 15 with remarkably high rate constants of oxidation (>3.5 × 107 M−1s−1) and hyperoxidation (~2 × 107 M−1s−1). The endoperoxide-hydroperoxide PGG2, an intermediate in prostanoid synthesis, oxidized HsPrx3 with a similar rate constant, but was less effective in causing hyperoxidation. Biophysical methodologies suggest that HsPrx3 can bind hydrophobic structures. Indeed, molecular dynamic simulations allowed the identification of a hydrophobic patch near the enzyme active site that can allocate the hydroperoxide group of fFA-OOHs in close proximity to the thiolate in the peroxidatic cysteine. Simulations performed using available and herein reported kinetic data indicate that HsPrx3 should be considered a main target for mitochondrial fFA-OOHs. Finally, kinetic simulation analysis support that mitochondrial fFA-OOHs formation fluxes in the range of nM/s are expected to contribute to HsPrx3 hyperoxidation, a modification that has been detected in vivo under physiological and pathological conditions.